Meningitis-associated pneumococcal serotype 8, ST 53, strain is hypervirulent in a rat model and has non-haemolytic pneumolysin which can be attenuated by liposomes - Müller, Annelies; Lekhuleni, Cebile; Hupp, Sabrina; du Plessis, Mignon; Holivololona, Lalaina; Babiychuk, Eduard; Leib, Stephen L.; Grandgirard, Denis; Iliev, Asparouh I.; von Gottberg, Anne; Hathaway, Lucy J. (Frontiers in Cellular and Infection Microbiology, 2023)
Streptococcus pneumoniae bacteria cause life-threatening invasive pneumococcal disease (IPD), including meningitis. Pneumococci are classified into serotypes, determined by differences in capsular polysaccharide and both serotype and pneumolysin toxin are associated with disease severity. Strains of serotype 8, ST 53, are increasing in prevalence in IPD in several countries. Here we tested the virulence of such an isolate in a rat model of meningitis in comparison with a serotype 15B and a serotype 14 isolate. All three were isolated from meningitis patients in South Africa in 2019, where serotype 8 is currently the most common serotype in IPD. Only the serotype 8 isolate was hypervirulent causing brain injury and a high mortality rate. It induced a greater inflammatory cytokine response than either the serotype 15B or 14 strain in the rat model and from primary mixed-glia cells isolated from mouse brains. It had the thickest capsule of the three strains and produced non-haemolytic pneumolysin. Pneumolysin-sequestering liposomes reduced the neuroinflammatory cytokine response in vitro indicating that liposomes have the potential to be an effective adjuvant therapy even for hypervirulent pneumococcal strains with non-haemolytic pneumolysin.